Tualang Honey Attenuates Noise Stress-Induced Memory Deficits in Aged Rats - Azman, Khairunnuur Fairuz; Zakaria, Rahimah; Aziz, Che Badariah Abdul; Othman, Zahiruddin (Hindawi Publishing Corporation, 2016)
Ageing and stress exposure may lead to memory impairment while oxidative stress is thought to be one of the underlying mechanisms involved.This study aimed to investigate the potential protective effects of Tualang honey supplementation on memory performance in aged rats exposed to noise stress. Tualang honey supplementation was given orally, 200mg/kg body weight for 28 days. Rats in the stress groupwere subjected to loud noise, 100 dB(A), 4 hours daily for 14 days.All ratswere subjected to novel object recognition test for evaluation of memory performance. It was observed that the rats subjected to noise stress exhibited significantly lower memory performance and higher oxidative stress as evident by elevated malondialdehyde and protein carbonyl levels and reduction of antioxidant enzymes activities compared to the nonstressed rats. Tualang honey supplementation was able to improve memory performance, decrease oxidative stress levels, increase brain-derived neurotrophic factor (BDNF) concentration, decrease acetylcholinesterase activity, and enhance neuronal proliferation in the medial prefrontal cortex (mPFC) and hippocampus. In conclusion, Tualang honey protects against memory decline due to stress exposure and/or ageing via enhancement of mPFC and hippocampal morphology possibly secondary to reduction in brain oxidative stress and/or upregulation of BDNF concentration and cholinergic system.